2018
DOI: 10.1007/s00170-018-1932-y
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing technology: the status, applications, and prospects

Abstract: Additive manufacturing (AM) has first emerged in 1987 with the invention of stereolithography. The AM is an important, rapidly emerging, manufacturing technology that takes the information from a computer-aided design (CAD) and builds parts in a layer-by-layer style. As this technology offers many advantages such as manufacturing of complex geometries, reducing manufacturing cost and energy consumption, it has transformed manufacturing from the mass production to the mass customization. Also, it has found wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 35 publications
0
48
0
3
Order By: Relevance
“…[ 8 ] Post‐processing can also be required for other materials such as polymers to modify the surface texture, degree of crosslinking, porosity, or residual stresses that ultimately affect the mechanical properties of the printed structure. [ 9 ] Most commonly, thermal treatment is the best choice; however, it is often the case that one or more of the device materials (including the substrate) is incompatible with heating and alternative approaches are required.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Post‐processing can also be required for other materials such as polymers to modify the surface texture, degree of crosslinking, porosity, or residual stresses that ultimately affect the mechanical properties of the printed structure. [ 9 ] Most commonly, thermal treatment is the best choice; however, it is often the case that one or more of the device materials (including the substrate) is incompatible with heating and alternative approaches are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high hardness and low machinability of Ti alloys affect their feasibility by conventional processes [3], encouraging the research for new methods, as pointed out in Reference [4], for vibration cutting. Machinability problems can be overcome by additive manufacturing, that includes a variety of technologies, applied for more than 20 years for porous structures and prototypes, some of which promise to become commonly used to produce near-net-shape components of complex geometry reducing production time and cost [5].…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging disruptive manufacturing technology, the application of AM technologies has increased substantially in different industries during the past years, and considerable research, from scientific and technological challenges [3,5,7] to business model innovation and industry application issues [2,4,[16][17][18], has been carried out. A prediction of the future of AM, based on an extensive Delphi survey by Jiang et al [1], indicated that, by 2030, a significant number of small and medium enterprises will share industry-specific additive manufacturing production resources to achieve higher machine utilization, learning effects, and quality assessments.…”
Section: Related Workmentioning
confidence: 99%
“…This characteristic of AM provides new opportunities for freedom of design and enables on-demand production of customized products without additional manufacturing costs due to the geometric complexity. The importance of AM technology has been recognized in various businesses [1,2,4,5] and has been considered as one of the key supporting technologies for smart design and manufacturing in Industry 4.0 [6]. The advantages of AM technology over traditional manufacturing have been identified and discussed by Attaran [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation